Abnormal electrocardiographic findings in athletes: recognising changes suggestive of primary electrical disease. Issue 3 (9th January 2013) - Drezner, Jonathan A; Ackerman, Michael J; Cannon, Bryan C; Corrado, Domenico; Heidbuchel, Hein; Prutkin, Jordan M; Salerno, Jack C; Anderson, Jeffrey; Ashley, Euan; Asplund, Chad A; Baggish, Aaron L; Börjesson, Mats; et al.
Abstract : Cardiac channelopathies are potentially lethal inherited arrhythmia syndromes and an important cause of sudden cardiac death (SCD) in young athletes. Other cardiac rhythm and conduction disturbances also may indicate the presence of an underlying cardiac disorder. The 12-lead ECG is utilised as both a screening and a diagnostic tool for detecting conditions associated with SCD. Fundamental to the appropriate evaluation of athletes undergoing ECG is an understanding of the ECG findings that may indicate the presence of a pathological cardiac disease. This article describes ECG findings present in primary electrical diseases afflicting young athletes and outlines appropriate steps for further evaluation of these ECG abnormalities. The ECG findings defined as abnormal in athletes were established by an international consensus panel of experts in sports cardiology and sports medicine.